Vaccination in Children With Autoimmune Disorders and Treated With Various Immunosuppressive Regimens: A Comprehensive Review and Practical Guide - Blanchard-Rohner, Geraldine (Frontiers in Immunology, 2021)
Children with autoimmune disorders are especially at risk of vaccine-preventable diseases due to their underlying disease and the immunosuppressive treatment often required for a long period. In addition, vaccine coverage remains too low in this vulnerable population. This can be explained by a fear of possible adverse effects of vaccines under immunosuppression, but also a lack of data and clear recommendations, particularly with regard to vaccination with live vaccines. In this review, the latest literature and recommendations on vaccination in immunosuppressed children are discussed in detail, with the aim to provide a set of practical guidelines on vaccination for specialists caring for children suffering from different autoimmune disorders and treated with various immunosuppressive regimens.